"Aid, trade and investment": Water operator partnerships and the Dutch water sector. (February 2023) - Beck, Andrea
The concept of water operator partnerships (WOPs) was first proposed by a United Nations (UN) advisory board in 2006. Since then, several hundred WOPs have been implemented within and across different world regions. In contrast to public-private partnerships, WOPs are aimed at facilitating peer-to-peer learning between water and sanitation operators on a not-for-profit basis. According to official UN discourse, "mentor" operators share their expertise out of solidarity and a commitment to enhancing the performance of their peers. However, in light of the controversial history of privatization in the water sector, critics have raised doubts about the role of solidarity as a mentor motivation. Why would water operators assist other providers free-of-charge? Is solidarity indeed the main motivation behind knowledge sharing and capacity building in WOPs, or are more self-interested, profit-oriented incentives driving these activities? This article engages with these questions by analyzing the case of Vitens Evides International (VEI), a public company from the Netherlands that has emerged as the most active "mentor" in North-South WOPs to date. Drawing on interviews with VEI managers, water company representatives, and other experts, I show that VEI's mentoring activities are driven by a complex array of motivations, including staff development and recruitment, customer relations, sustainable development, and the advancement of opportunities for trade and investment. Some of these motivations are closely intertwined with Dutch development policy and the promotion of Dutch water expertise. More research is needed to understand how these interests and motivations affect social equity, learning, and capacity development in WOPs.